An in-depth evaluation of frequency-aware scheduler for improving user experience on mobile devices - Tran, Giang Son; Carlier, Axel; Hagimont, Daniel (Journal of Computer Science and Cybernetics, 2022)
Mobile devices are more and more invading our daily life. Users of such devices expect to have a good experience, which is mainly linked with performance. However, higher performance also means a reduction in battery life, negatively contributing to the overall user experience. A common way to balance this performance-battery trade-off is to reduce CPU frequency when underload with Dynamic Voltage and Frequency Scaling. In our previous work, we introduced a Frequency-Aware Completely Fair Scheduler (called FA-CFS), which helps in reducing battery consumption and increasing the smoothness of mobile interface browsing. However, the current evaluation of FA-CFS model is only at quantitative results of power consumption rather than user experience on using their mobile device. In this paper, we perform an in-depth evaluation of the FA-CFS model, both quantitative results for system performance evaluation and qualitative results for user experience on mobile device usage. The experiments show that FA-CFS can reduce the rate of interface frame time peaks by up to 40% in terms of quantitative results and obtains a quantifiable impact on the quality of user experience with a quicker, more responsive interface.